The Dichotomy of Cold and Heat in the Packaging of Stumbras Vodka Premium Organic - Kavarskas, Edvardas (Semiotika, 2016)
Over the last few decades we may discover and follow the significant changes extending in the segment of vodka. The globalgrowth of vodka usage publicly proportionally supplements the demand of the image value. The appearance of luxury category required sophistication and legitimation of vodka in the context of the noble spirits that already had high standards for both – their image and storytelling. To add more, in the past few years dozens of organic vodkas entered the global market. AB “Stumbras” – the largest Lithuanian alcoholic beverages producer was the first company to step out with the organic vodka label in Lithuania. Although “Stumbras Vodka Premium Organic” is not in a competition with “Grey Goose” or “Belvedere” in the terms of price, yet is a number one candidate to the title of the most expensive Lithuanian serial vodka. The answer of the question on what actually inspires the appearance of exclusive, highly priced vodkas, is hidden behind the stories and legends that are and will always be the most essential part of super premium segment products. People like listening to stories as well as telling them. And this could be done not only via text, but also images. In the spirits market – images first, are acknowledged and understood as packaging. Form, label and material used stimulates not only visible reflects, but also the senses of touching and even listening. This article will give us a closer look to the “Stumbras Vodka Premium Organic” packaging legend over the prism of visual semiotics. The habitual methodological instruments used in visual semiotics – the analysis of plastic dimension and figurative level – layer after layer opened the inspirations and metaphors of the creative team. It also gave an opportunity to identify the visual oppositions and tension, felt in compositions that are found in the work. The article reveals topologic, chromatic, eidetic and textural characteristics of the visual part. Typefaces typology as well as the semantic messages found in the design are also analyzed. Additional attention is focused on the fund inspiration of the creative team – flax, as “Stumbras Vodka Premium Organic” is represented as “the only Lithuanian vodka filtered through flax” and flax plays an exceptional role in the mythological consciousness of Lithuanians. The end of the article synthesizes the cohesion between analyzed plots in order to find semi-symbolism. It also seeks for the answer to the question if the particular packaging adequately represents content and the target audience. First, the parsing supplements the following allegation: the hotter vodka, the colder packaging it comes with. Based on this paradox visual text is created, which at the end is actually the vodka packaging design. Second, it reveals friction of the fundamental gender stereotypes and confirms the esthetical requirements brought by the millennial generation. The concept and its implementation appear in the luxury of less design.